2023
DOI: 10.1128/spectrum.03943-22
|View full text |Cite
|
Sign up to set email alerts
|

Epitranscriptomic N 6 -Methyladenosine Profile of SARS-CoV-2-Infected Human Lung Epithelial Cells

Abstract: Posttranscriptional modification of viral and cellular RNA by N 6 -methyladenosine (m 6 A) plays an important role in regulating the replication of many viruses and the cellular immune response to infection. We therefore sought to define the epitranscriptomic m 6 A profile of human lung epithelial cells infected with SARS-CoV-2.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…m6A reader genes show uneven expression levels, suggesting that the stability of specific transcripts is usually restricted in AD brains [ 28 ]. Different patterns of these m6A regulators can lead to an aberrant post-transcriptional modification environment [ 29 ], which may alter the expression of AD-related genes. Specifically, we observed a significant downward trend in METTL3 in AD brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…m6A reader genes show uneven expression levels, suggesting that the stability of specific transcripts is usually restricted in AD brains [ 28 ]. Different patterns of these m6A regulators can lead to an aberrant post-transcriptional modification environment [ 29 ], which may alter the expression of AD-related genes. Specifically, we observed a significant downward trend in METTL3 in AD brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional availability of cancer cells in the tumor micro-environment constantly changes during tumor progression, whereby they can utilize abundant lipids to promote rapid cell growth [ 19 , 20 ]. Studies have shown that m6A modification dynamically changes with the external environment [ 21 , 22 ]. For instance, a high-fat environment can lead to changes in m6A-related molecules.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Stacia et al. [ 69 ] defined the m 6 A modification profile in SARS-CoV-2-infected cells, identifying various mRNA and noncoding RNA species with differential m 6 A modifications, further enriching our understanding of the virus’s interaction with host cell mechanisms.…”
Section: Sars-cov-2 As a Paradigm For M 6 A Epitra...mentioning
confidence: 99%